Autologous haematopoietic stem cell transplantation for aggressive multiple sclerosis: the Swedish experience. Issue 10 (19th February 2014) - Burman, Joachim; Iacobaeus, Ellen; Svenningsson, Anders; Lycke, Jan; Gunnarsson, Martin; Nilsson, Petra; Vrethem, Magnus; Fredrikson, Sten; Martin, Claes; Sandstedt, Anna; Uggla, Bertil; Lenhoff, Stig; et al.
Abstract : Background: Autologous haematopoietic stem cell transplantation (HSCT) is a viable option for treatment of aggressive multiple sclerosis (MS). No randomised controlled trial has been performed, and thus, experiences from systematic and sustained follow-up of treated patients constitute important information about safety and efficacy. In this observational study, we describe the characteristics and outcome of the Swedish patients treated with HSCT for MS. Methods: Neurologists from the major hospitals in Sweden filled out a follow-up form with prospectively collected data. Fifty-two patients were identified in total; 48 were included in the study and evaluated for safety and side effects; 41 patients had at least 1 year of follow-up and were further analysed for clinical and radiological outcome. In this cohort, 34 patients (83%) had relapsing-remitting MS, and mean follow-up time was 47 months. Results: At 5 years, relapse-free survival was 87%; MRI event-free survival 85%; expanded disability status scale (EDSS) score progression-free survival 77%; and disease-free survival (no relapses, no new MRI lesions and no EDSS progression) 68%. Presence of gadolinium-enhancing lesions prior to HSCT was associated with a favourable outcome (disease-free survival 79% vs 46%, p=0.028). There was no mortality. The most common long-term side effects were herpes zoster reactivation (15%) and thyroid disease (8.4%). Conclusions: HSCT is a very effective treatment of inflammatory active MS and can be performed with a high degree of safety at experienced centres.